VD_FINDINFO Jug / 2014 / 49 vom 10. Dezember 2013 - VD Tribunal cantonal (2013)
MISE À BAN GÉNÉRALE, DÉNONCIATEUR, CONTRAVENTION, CONTRAVENTION DE POLICE DE DROIT CANTONAL | 13 LContr, 105 CPP (CH), 301 CPP (CH), 44 CDPJ, 30 LVCPP